Asylum seekers, Ireland, and the return of the repressed. Issue 1 (2nd January 2016) - Lentin, Ronit
Abstract: In 2014 residents in Direct Provision Centres for asylum seekers staged a series of protests. The protests, which coincided with the appointment of a new Minister for Justice who announced the Irish government's plans to reform the asylum system, voiced three clear demands. Firstly, the protestors demanded that all asylum centres be closed; secondly, they demanded that all residents be given the right to remain and work in Ireland; and thirdly, they demanded an end to all deportations. The government's response to these protests was to appoint a working group in October 2014, made up of representatives of migrant-support NGOs (but without any significant representation of asylum seekers themselves) while also announcing that it intends to reform rather than abolish the system. Against this background, this paper makes three interlinked theoretical propositions. Firstly, I propose that just as the Irish state and society managed to ignore workhouses, mental health asylums, "mother and baby homes", Magdalene laundries and industrial schools, they also "manage not to know" of the plight of asylum seekers, precisely because the Direct Provision system isolates asylum applicants, makes them dependent on bed and board and a small "residual income maintenance payment to cover personal requisites", and makes it difficult for them to organise on a national level. "Managing not to know", or disavowing, entails the erasure of the Direct Provision system from Ireland's collective consciousness at a time when increasing emigration is returning to haunt Irish society after years of refusing to confront the pain of emigration. I argue that asylum seekers represent the return of Ireland's repressed that confronts Irish people, themselves e/migrants par excellence. Secondly, I propose that by taking action and representing themselves, the residents of Direct Provision Centres can no longer be theorised as Agamben's "bare life", at the mercy of sovereign power, to whom everything is done and who are therefore not considered active agents in their own right. The third proposition responds to the theme of this special issue, that multiculturalism is "in crisis", arguing in the conclusion that this "crisis" hardly applies to Ireland, where the brief flirtations with "interculturalism" by state, society but also Irish studies disavow race and racism in favour of a returning obsession with emigration, which enables the continued disavowal of the experiences of asylum seekers in Direct Provision.